Effect of the Ortho Alkylation of Perylene Bisimides on the Alignment and Self‐Assembly Properties. Issue 4 (9th July 2014) - Dasgupta, Debarshi; Kendhale, Amol M.; Debije, Michael G.; ter Schiphorst, Jeroen; Shishmanova, Ivelina. K.; Portale, Giuseppe; Schenning, Albertus P. H. J.
Abstract The effect of the ortho alkylation of perylene bisimides on the alignment and self‐assembly properties has been studied. It was found that the dichroic properties of perylene bisimides in a liquid crystal host can be reversed with a single synthetic step by ortho alkylation. Furthermore, a solvent‐induced growth of ultralong organic n‐type semiconducting fibrils from non‐ortho‐alkylated perylene bisimide was observed. Ortho substitution of the perylene bisimide core alters the mode of fibrillar growth, leading to isotropic crystallization.